PERFORMANS PEDET SAPI ACEH HASIL KAWIN ALAM DENGAN INSEMINASI BUATAN (IB) DI BPTU-HPT INDRAPURI - Rahayu, Sri; Haqqi, Amirul (Jurnal Sains Riset, 2022)
This researched aims to compared the birth performance of Aceh cattle resulted natural mating and artificial insemination mating at BPTU-HPT Indrapuri. The Aceh calves  used in this study amounted to 14 calves. This research uses quantitative methods and the data obtained by t test. The parameters measured from the performance of Aceh cattle calves are: shoulder height (cm), body length (cm), and chest shoulder height (cm). The average value of the shoulder measurement of natural mating calves is 55.50 cm while the results of artificial insemination mating is 59.71 cm, the average body length of natural mated calves is 48.79 cm while the results of artificial insemination mating is 54.29 and the average chest circumference is the calves. natural mating 54.21 cm while the result of artificial insemination  mating 58.14 cm.  Based on the average value and the results of statistical tests, the birth performance of Aceh cattle with natural mating and artificial insemination mating showed a significant difference (P0.05) where the birth performance of artificial insemination mating better than that of natural mating.Keywords : Shoulder height, body length, chest circumference, calves, Aceh cattle, natural mating, artificial insemination (IB)